The silent sea [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Oregon files adventures., 2010)
On December 7th, 1941, five brothers exploring a small island off the coast of Washington State make an extraordinary discovery, only to be interrupted by news of the Pearl Harbor attack. In the present, Cabrillo, chasing the remnants of a crashed satellite in the Argentina, stumbles upon a shocking revelation of his own. His search to untangle the mystery leads him to that small island and its secret.